Early pseudoprogression and progression lesions in glioblastoma patients are both metabolically heterogeneous - Ungan, Gülnur; Pons‐Escoda, Albert; Ulinic, Daniel; Arús, Carles; Ortega‐Martorell, Sandra; Olier, Ivan; Vellido, Alfredo; Majós, Carles; Julià‐Sapé, Margarida (NMR in biomedicine, 2024)
The standard treatment in glioblastoma includes maximal safe resection followed by concomitant radiotherapy plus chemotherapy and adjuvant temozolomide. The first follow‐up study to evaluate treatment response is performed 1 month after concomitant treatment, when contrast‐enhancing regions may appear that can correspond to true progression or pseudoprogression. We retrospectively evaluated 31 consecutive patients at the first follow‐up after concomitant treatment to check whether the metabolic pattern assessed with multivoxel MRS was predictive of treatment response 2 months later. We extracted the underlying metabolic patterns of the contrast‐enhancing regions with a blind‐source separation method and mapped them over the reference images. Pattern heterogeneity was calculated using entropy, and association between patterns and outcomes was measured with Cramér's V. We identified three distinct metabolic patterns—proliferative, necrotic, and responsive, which were associated with status 2 months later. Individually, 70% of the patients showed metabolically heterogeneous patterns in the contrast‐enhancing regions. Metabolic heterogeneity was not related to the regions' size and only stable patients were less heterogeneous than the rest. Contrast‐enhancing regions are also metabolically heterogeneous 1 month after concomitant treatment. This could explain the reported difficulty in finding robust pseudoprogression biomarkers. In a retrospective study with 31 glioblastoma patients 1 month after concomitant treatment, we identified three metabolic patterns with MRS, in contrast‐enhancing regions with suspicions of progression. One pattern is proliferative, the second is necrotic, and the third has necrotic lipids and a polyunsaturated fatty acid peak. Although the patterns are associated with outcome 2 months later, they are not fully predictive due to intra‐patient heterogeneity. The heterogeneity observed is not linked either to progression or to the contrast‐enhancing regions' size.